2014
DOI: 10.1149/2.0461414jes
|View full text |Cite
|
Sign up to set email alerts
|

An Isothermal Model for Predicting Performance Loss in PEMFCs from Balance of Plant Leachates

Abstract: A model is presented for the contamination of a proton exchange membrane fuel cell (PEMFC), including adsorption onto the Pt catalyst, absorption into the membrane, and ion exchange with ionomeric components. Model predictions for three sources of voltage loss account for the two-dimensional, time-dependent contamination along the channel and into the membrane. The model is developed by considering the well-known concepts of Langmuir adsorption, partition coefficients, plug flow reactors (PFRs), and dimensionl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…These results have the same trends as ex-situ adsorption isotherm of 2,6-DAT reported by Cho et al 38 The maximum value for θ 1 reported in Figure 7 Figure 9. The rate of ionomer poisoning during contamination γ ic with 2,6-DAT.…”
Section: Effectsupporting
confidence: 87%
“…These results have the same trends as ex-situ adsorption isotherm of 2,6-DAT reported by Cho et al 38 The maximum value for θ 1 reported in Figure 7 Figure 9. The rate of ionomer poisoning during contamination γ ic with 2,6-DAT.…”
Section: Effectsupporting
confidence: 87%
“…These parameters can be used for the prediction of performance loss in PEMFCs using the previously developed model. 53,83 Interestingly, the maximum coverages for aniline, benzene, and DATs (i.e., 0.55-0.65) were equal within the accuracy of these data. Note that as described in Ref.…”
Section: Resultssupporting
confidence: 52%
“…Note that as described in Ref. 83, the coverage (θ) and equilibrium concentration (K eq ) of contaminant A at the interface (C * A ) between the gas diffusion layer and the catalyst layer can be expressed by the Langmuir adsorption isotherm as below: where B is the maximum coverage measured by ex-situ isotherms; C A * is the concentration of contaminant A at the midpoint of the electrode [mol/cm 3 ]; C AS is the average concentration of the adsorbed contaminant A on the Pt sites [mol/cm 2 ]; C s sis the surface concentration of Pt sites [mol/cm 2 ]; and K eq is the equilibrium constant for the Langmuir isotherm [cm 3 /mol].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations